Mathematical modelling of the heart: cell to organ - Smith, N; Mulquiney, P; Nash, M; Bradley, C; Nickerson, D; Hunter, P (2002)
Single cell and whole organ mathematical models of cardiac electrophysiology, mechanics and metabolism are presented. The important elements of each model are outlined and, in particular, the methods, techniques and considerations for coupling each element together to create an integrated cardiac model are discussed. Results for both individual tissue and whole organ simulations are presented along with preliminary results from coupled models. (C) 2002 Published by Elsevier Science Ltd.